Novel and green nanocomposite-based adsorbents from functionalised mesoporous KCC-1 and chitosan-oleic acid for adsorption of Pb(II). (October 2019) - Zarei, Fatemeh; Marjani, Azam; Soltani, Roozbeh
Graphical abstract: Highlights: Green and efficient polymer matrix nanocomposite-based adsorbents were fabricated. The adsorbents (designated as TA-KCC-1/Chi-OLA NCs) were used for uptake of Pb(II). A facile and effective method was used for fabrication of TA-KCC-1/Chi-OLA NCs. Chitosan and oleic acid used in TA-KCC-1/Chi-OLA NCs makes it a green adsorbent. The adsorption capacity of TA-KCC-1/Chi-OLA for Pb(II) was found to be 168 mg g −1 . Abstract: To capture heavy metals in aqueous solution, it is imperative to develop viable and safe heavy metals uptake techniques. Herein, we report polymer matrix nanocomposite adsorbents with 2 and 5 wt.% nanofiller contents based on functionalised mesoporous fibrous silica KCC-1, chitosan, and oleic acid (abbreviated as TA-KCC-1/Chi-OLA NC). TA-KCC-1/Chi-OLA NCs relying on physicochemical adsorption are potential candidates for heavy metals removal because of their facile fabrication procedure, low toxicity, biodegradability, and high affinity toward heavy metals. The adsorption of Pb(II) cations onto green TA-KCC-1/Chi-OLA 5 wt.% adsorbent was studied in the batch system. Langmuir and pseudo-second-order models were found to be the best fit models to predict isotherms and kinetics of adsorption, respectively. The maximum adsorption capacity according to the Langmuir model was 168 mg g −1 (adsorption conditions: pH: 9.0, adsorbent dose: 20.0 mg; contact time: 100 min; initial concentration: 100 mg L −1 ).